Uncertainty in risk issues for carbon capture and geological storage: Findings from a structured expert elicitation - Patricia Larkin; Robert Gracie; Ali Shafiei; Maurice Dusseault; Mirhamed Sarkarfarshi; Willy Aspinall; Daniel Krewski (International Journal of Risk Assessment and Management (Inderscience Publishers), 2019)
Carbon capture and geological storage (CCS) is identified within the portfolio of mitigation options for climate change. Each value chain activity of large scale integrated projects (capture, transport, injection and storage) includes uncertainties and hence potential risks with respect to both environmental and human health protection. With a focus on injection and storage, a structured elicitation of international experts provides quantified judgements and uncertainties and understanding of relative risk of CCS activities. In the 0–50 year, 51–499 year and >500 year time periods, the expert panel suggested an almost equal likelihood of storage leakage occurring, with a marked decrease from minor to major to catastrophic leakage (approximately >1 in 30; 1 in 10³; 1 in 10⁴, respectively); for the same time periods, the judgement of likelihood for major leakage that would result in measurable negative effects on human health or the environment was the same (approximately 1 in 10³). Insights could stimulate further scientific deliberations about the reliable and effective deployment of this complex and interdisciplinary technological process. A companion paper discusses complementary findings for issues in CCS risk management.
Keywords: carbon capture and storage; expert elicitation; risk assessment; uncertainty quantification; environmental health; geological injection; geological sequestration; type of access: open access